Efforts to Legalize Cannabis for Medicine, Reviewed from Legal Sociology - Muh. Nasir (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Indonesia as a country that adopted  the 1961 Single Convention on Narcotics and the Protocol that changed it, refers to Political principles. Which was ratified  by Law No. 35 of 20009 concerning narcotics. Narcotics abuse is prohibited and threatened with imprisonment as well as narcotics addicts who do not report to recover are also threatened with criminal punishment, but the coercive effort and punishment are in the form of rehabilitation. Modern medicine  is a method of treatment that is carried out based on scientific  research and based on knowledge from various aspects, medical  treatment uses several applied scientific disciplines in treating a disease, the way of examining and diagnosing diseases is more accurate. The problem in this study is how  can the potential legalization of cannabis for treatment be realized in Indonesia? How can  the legalization of marijuana for treatment be applied in Indonesia? The objectives of this research are. To find out and analyze whether the potential for legalization of cannabis for treatment can be realized in Indonesia. The research method used is  a normative  research method through a library research approach or a literature review method using  the analytical descriptive writing method. From the results of the data collected from the laboratory research.The results of the study show that. The legalization of marijuana for treatment can be realized in Indonesia in terms of existing laws, in Law No. 35 of 2009 Health Law No. 17 of 2023 article 139. Judging from the benefits,  the Narcotics  Law and the Health Law, and Islamic religious law are allowed, which through   mechanisms or exceptions under certain conditions are allowed, and also from sociology of society there are also marijuana used in daily life. In the application or implementation of the legalization of marijuana for treatment, there are several factors that hinder  the legalization of marijuana for treatment, the Convention